The culm and glume anatomical study on Lolium (Poaceae) species in Iran - Keshavarzi, Maryam; Bokaee, Zahra Nazem; Derakhshan, Neda (Acta Biologica Szegediensis, 2022)
Lolium (Poaceae) is composed of five species in Iran that are of forage and weed importance. Culm and glume anatomy of grasses is inadequately explored. In the present study culm and glume anatomical structures of 17 population of four Lolium species is considered by use of 16 qualitative and quantitative features to distinguish Lolium species in Iran and to determine their diagnostic value. The culm cross-section showed multilayered hypodermis, ribbed or un-ribbed culm cross-sections, cuticles with different thicknesses, and the cortex with different tissues. Vascular bundles are arranged in two to more rings in the culm anatomy. Glume anatomical observations showed differences in girder attachment to vascular bundles, the outline of the cross-section, and the cortex tissue composition. The multi-variate statistical method based on culm and glume anatomical features showed that L. perenne and L. multiflorum are grouped near each other but there is more mixture between L. persicum and L. rigidum. Our findings are in agreement with the grouping pattern achieved by previous researches on leaf anatomy and lemma and palea micro-morphology of the same species. The molecular study by ISSR also provides support for the present study. The culm and glume anatomy of species studied provides valuable data for taxonomic purposes.